4, 5, 7‐Trisubstituted indeno[1, 2‐b]indole inhibits CK2 activity in tumor cells equivalent to CX‐4945 and shows strong anti‐migratory effects. Issue 2 (18th December 2021) - Birus, Robin; El‐Awaad, Ehab; Ballentin, Laurens; Alchab, Faten; Aichele, Dagmar; Ettouati, Laurent; Götz, Claudia; Le Borgne, Marc; Jose, Joachim
Abstract : Highly pleiotropic and constitutively active protein kinase CK2 is a key target in cancer therapy, but only one small‐molecule inhibitor has reached clinical trials—CX‐4945. In this study, we present the indeno[1, 2‐ b ]indole derivative 5‐isopropyl‐4‐methoxy‐7‐methyl‐5, 6, 7, 8‐tetrahydroindeno[1, 2‐ b ]indole‐9, 10‐dione (5a‐2 ) that decreased the intracellular CK2 activity in A431, A549, and LNCaP tumor cell lines analogous to CX‐4945 (> 75% inhibition at 20 µm ) and similarly blocked CK2‐specific Akt phosphorylation in LNCaP cells. Cellular uptake analysis demonstrated higher intracellular concentrations of 5a‐2 (408.3 nm ) compared with CX‐4945 (119.3 nm ). This finding clarifies the comparable effects of both compounds on the intracellular CK2 activity despite their different inhibitory potency in vitro [IC50 = 25 nm (5a‐2 ) and 3.7 nm (CX‐4945)]. Examination of the effects of both CK2 inhibitors on cancer cells using live‐cell imaging revealed notable differences. Whereas CX‐4945 showed a stronger pro‐apoptotic effect on tumor cells, 5a‐2 was more effective in inhibiting tumor cell migration. Our results showed that 49% of intracellular CX‐4945 was localized in the nuclear fraction, whereas 71% of 5a‐2 was detectable in the cytoplasm. The different subcellular distribution, and thus the site of CK2 inhibition, provides a possible explanation for the different cellular effects. Our study indicates that investigating CK2 inhibition‐mediated cellular effects in relation to the subcellular sites of CK2 inhibition may help to improve our understanding of the preferential roles of CK2 within different cancer cell compartments. Abstract : In this study, a 4, 5, 7‐trisubstituted indeno[1, 2‐ b ]indole, 5a‐2, is shown to inhibit CK2 activity in cancer cells equivalently to the well‐known inhibitor CX‐4945. Whereas CX‐4945 shows strong pro‐apoptotic and anti‐proliferative effects, we demonstrate a strong anti‐migratory effect for 5a‐2 . We conclude that subcellular localization might be critical for the differential cellular effects of CK2 inhibitors.